Cognitive Biases and Their Impact on Strategic Business Decisions - Taksande, Bipin (Digital Repository of Theses, 2025)
This research explores how cognitive biases influence strategic decision-making in businesses and management. It draws from a wide range of previous literature to comprehensively understand how cognitive biases shape decision-making outcomes over time. It also examines the long-term effects of these biases on organisational sustainability and performance. By analysing the literature from the perspective of cognitive biases, the goal is to provide practical insights for businesses aiming to improve their strategic decision-making methods and long-term performance sustainability in a complex and uncertain environment. The central question is: How do cognitive biases affect an organisation's long-term sustainability and performance, and what strategies should they use to reduce their impact on strategic decision-making?